Agro-morphological characterization of Arabica coffee cultivars in Burundi - Ndikumana, J.; Mwangi, M.; Wainaina, C.; Kufa Obso, T. (Science Alert, 2021)
Background and Objective: Arabica coffee is an important beverage crop in world trade. The crop is gaining increasing importance in Burundi as an export crop. This study aimed to evaluate diversity among coffee cultivars based on quantitative agro-morphological traits for developing superior cultivars in Burundi. Materials and Methods: Fifteen coffee accessions including five commercial cultivars) were used in the study. From each accession, data were collected from three randomly selected trees on 17 quantitative agro-morphological traits and subjected to various statistical analyses including, analysis of variance (ANOVA), PCA biplot and cluster analysis. Results: The analysis of variance showed significant differences (p<0.05) among the accessions for most of the quantitative traits studied. Considering the number of fruits per internode and percentage of fruit-bearing primary branches, the highest yielding accessions were SL28, Mysore and S795. PCA showed that four principal components namely, PC1(33.70), PC2(30.57), PC3(10.21) and PC4(9.15) explained about 83.63% of the total variation. Cluster and distance analysis of quantitative traits revealed the existence of three different groups. The number of accessions in each group was 3, 3 and 9 for clusters I, II and III respectively. The maximum distance was seen between clusters I and II (88) while the minimum was seen between I and III (23). Conclusion: The results show wide diversity among the 15 coffee genotypes grown in Burundi concerning most quantitative morphological traits studied. The genotypes were grouped into three clusters where, Cluster II and III contained genotypes with valuable quantitative agronomic traits, while most of the accessions in cluster I exhibited poor agronomic performance.